PENERAPAN MEDIA PEMBELAJARAN INOVATIF DALAM PEMBELAJARAN MATEMATIKA SEKOLAH DASAR DI PGSD UPP TEGAL - Andrijati, Noening (Universitas Negeri Semarang, 2014)
Phenomena in elementary mathematics instruction indicates that there is a tendency of media use by teachers is not optimal, the media used is very simple and does not attract the attention of students. Innovative media, as an idea, practice, or object that is considered new media, including Macromedia Flash and puzzles. This study aimed to obtain information regarding: 1) the application of innovative media; 2) the role of the media (innovative); and 3) the impact of the application of innovative media in learning mathematics. Approach to qualitative research conducted two studies to assess student thesis on the application of media PGSD inovaif in learning elementary school mathematics. Subjects in this study included 25 fourth grade students of SD Negeri Tegalsari 4 and 31 second grade students of SD Negeri Tegal Kemandungan 03, as well as the teacher researcher and observer respectively by 2 people. Data collection techniques using the techniques of documentation, observation, and interviews. Data analysis was performed through the stages of data reduction, data display and conclusion drawing or verification. Based on the results of research and discussion it is concluded that: 1) In general, innovative media in teaching elementary mathematics applied through the stages of introduction, the core and the cover. Learning the nuances of the game, load simulation or manipulation, and working in group ; 2) the presence of the media (innovative) is required at the stage of elaboration (explanation of the concept) in core activities, as clarification and confirmation of the core activities and cover; and 3) the impact of the application of innovative media for teachers and students, which is increasing the ability of teachers to hold and use the media, organizing materials and managing instructional time effectively; increasing studentsâ learning activities (student involvement in student learning and persistence in completing the task group / individual).